Respostas fisiológicas do coqueiro anão verde sob diferentes lâminas de irrigação - Araújo, Beatriz de Abreu (2019)
The dwarf coconut tree presents a high water demand, requiring an annual precipitation of 1500 mm, with a uniform distribution. The Northeast, specifically in the state of Ceará, is characterized by the occurrence of drought periods and a poor distribution of rainfall in the period that corresponds to the rainy season of the region, thus this rainfall variability and inadequate irrigation management are classified as one of the main causes of low productivity of the coconut tree, even where its cultivation is common. However, the study of the physiological behavior of green dwarf coconut plants becomes relevant in order to evaluate the responses of this crop to different water availability conditions, observing their physiological behavior against the use of deficient and excess blades applied via localized irrigation. The experiment was carried out in the field for two years in an area under organic cultivation of the company Ducoco Alimentos Saudáveis, in the municipality of Camocim, Ceará, Brazil. The experimental design was in randomized blocks in a two-factor factorial, the first being the irrigation depths estimated from the reference evapotranspiration and the crop cultivation coefficients (50%, 75%, 100% and 125% of ETc) and the second the evaluation months. Leaf water potential variables, gas exchange, total soluble carbohydrates, leaf mineral nutrition, fruit yield and quality and water productivity were evaluated. Leaf water potential was not influenced by water treatments and was more negative in the months corresponding to the end of the dry season; gas exchange was higher during the rainy season, regardless of the amount of water that was applied during the dry season; It was observed variation of the nutritional state of the plants in the contents of P, Ca, S and Cu of which presented a growth tendency with the increase of the irrigation depth; Fruit weight was not influenced by water treatments; The volume of coconut water increased with increasing irrigation depth and the smaller amounts were produced in the driest months of the year; The water use efficiency of the green dwarf coconut tree decreased as the amount of water applied by irrigation increased.